2016
DOI: 10.1097/gco.0000000000000293
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of robotics in benign gynecologic surgery

Abstract: Advances in robotic technology such as the single-site platform and telesurgery, have the potential to revolutionize the field of minimally invasive gynecologic surgery. Higher quality evidence is needed to determine the advantages and disadvantages of robotic surgery in benign gynecologic surgery. Conclusions on the benefits and risks of robotic surgery should be made with caution given limited data, especially when compared with other routes. Route of surgery selection should take into consideration the surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 59 publications
0
34
0
4
Order By: Relevance
“…These trends are noteworthy. Robot‐assisted laparoscopy has several advantages over conventional laparoscopy such as improved ergonomics, a wider range of motion and dexterity, and greater ease of intracorporeal suturing . It has also been suggested that robot‐assisted surgery could serve as a better tool for general gynecologists to transition to advanced laparoscopic procedures such as RAM .…”
Section: Discussionmentioning
confidence: 99%
“…These trends are noteworthy. Robot‐assisted laparoscopy has several advantages over conventional laparoscopy such as improved ergonomics, a wider range of motion and dexterity, and greater ease of intracorporeal suturing . It has also been suggested that robot‐assisted surgery could serve as a better tool for general gynecologists to transition to advanced laparoscopic procedures such as RAM .…”
Section: Discussionmentioning
confidence: 99%
“…With advances in technology and surgical skill with robotic surgical equipment, more complex GYN and GYN‐oncology surgeries are now being completed as minimally invasive procedures, which results in a shorter length of stay and decreased patient morbidity . The resulting change in operative acuity necessitates that perioperative nurses must continually reassess and adjust roles and responsibilities as more procedures are moved from the inpatient operative setting to an ambulatory surgical site.…”
Section: Obstetrics and Gynecology (Ob‐gyn) Patient Carementioning
confidence: 99%
“…Another advantage of the robotic single-site platform may be its shorter learning curve when compared with single-site laparoscopic hysterectomy 26. At this time, the preliminary outcomes reported for single-site robotic hysterectomy appear promising, but most authors agree that more studies are needed to define the appropriate applications for this approach prior to widespread adoption 27. In particular, at this time, the single-site robotic platform is unlikely to replace the multiport robotic platform when operating cases with high surgical complexity.…”
Section: Single-site Hysterectomy Via Laparoscopic and Robotic Approachmentioning
confidence: 99%